Optimization of Active Open Space Use at Al-Hidayah Musalla Design Concept - Sri Winarni; Putri Herlia Pramitasari; Maria Istiqoma (ESE International Journal (Environmental Science and Engineering), 2021)
The use of active open space is one way to improve the value of environmental quality to be more optimal. It could be seen that RT. 06 RW. 05 Penanggungan Village, Malang, had an active open space in the form of contoured land that was not functioning properly. For this reason, the purpose of this study was to utilize this active open space as a forum for religious and social activities in Al-Hidayah Musalla (Islamic prayer room). The research method employed was a qualitative descriptive method with the object study approach of Musalla (Islamic prayer room) design concept. The results of this design concept were optimized for limited land use through function and space efficiency as well as optimization of green space on steep contoured land in the form of vertical gardens so that the existing land could have functioned optimally as active and contextual land with the surrounding environment.